[OP.5C.03] HIGHER PREVALENCE OF HYPERTENSION IN MIGRANTS IN ITALY: A SNAPSHOT OF THE 2012 AND 2013C WORLD KIDNEY DAY. (September 2016) - Clementi, A.; Buiatti, M.; Mussinelli, R.; Salinaro, F.; Andreucci, V.E.; Balducci, A.; Perrone, T.; Esposito, P.; Perlini, S.
Abstract : Objective: Among the many health-related challenges posed by the increased number of Migrants, cardiovascular risk evaluation has been less extensively evaluated than communicable disease prevention and treatment. Ethnic background is one of the many non-modifiable determinants of cardiovascular disease, whereas stress and modifiable factors such as dietary habits and smoking are very likely to be profoundly altered in the migrant population. Design and method: To compare the prevalence of hypertension in Italian residents as compared with Migrants, a total of 6027 voluntary subjects underwent medical interview, body weight, height and blood pressure (BP) measurement, risk factor evaluation and urine analysis during the National Kidney Day survey held in 2012 and 2013 by the Federazione Italiana del Rene (FIR). Results: Migrants were 445/6027 (7.38%), with a rate remarkably similar to the percentage of non-Italian residents (8.09%). A wide heterogeneity was evident, with 53 different nationalities, subdivided in Eastern Europe (38.2%), Northern Africa (17.6%), Center and Southern Africa (12.9%), Latin America (12.8%), Indian subcontinent (9.6%), Far East (5.5%), Middle East (3.4%) macro-areas. Gender distribution and body mass index were comparable in the Italian and in the Migrant groups. Despite a 10-year age difference (50 ± 12 vs. 41 ± 15 years; p <0.001), the overall prevalence of hypertension was similar in the two groups (44.7% in Italians vs. 43.4% in Migrants), as defined by BP>140/90 mmHg and/or current antyhypertensive treatment. When stratified by age, Migrants presented significantly higher BP values, the prevalence of hypertension being at least 10% higher than in Italian residents in any decade group. A similar trend was observed for awareness, active treatment and satisfactory BP control rates. Also the rate of proteinuria and glycosuria was higher in the spot urine sample analysis. Conclusions: In Migrants, hypertension prevalence, treatment rate and control rate are significantly higher than in the Italian resident population. In the future years this will inevitably increase the burden of cardiovascular disease on society and health system. These data underscore the urgent need of prevention and intervention in this special population, trying to take into proper account all the involved social, cultural, economic and health-related factors.